Effects of led lighting training on response time in Greco-Roman wrestlers - Gierczuk, D.; Bujak, Z.; Cieslinski, I. (Polish Journal of Sport and Tourism, 2023)
Introduction. Response time is one of the determinants of performance effectiveness in wrestling competitions. Its high levels help wrestlers fight more effectively when performing appropriate technical and tactical actions. Different factors such as a proper warm-up, unexpected situations, muscle fatigue, asthenic reactions, competition prestige and previous injuries may exert an influence on perceptual abilities (including RT and MT) and affect fighting effectiveness. Getting to know determinants of response time may provide a lot of valuable practical information that can be used in wrestling-related training. The study sought to determine changes in response time in Greco-Roman wrestlers produced by LLT.